THE POTENCY OF JAVANESE TURMERIC (CURCUMA XANTHORRHIZA ROXB.) ETHANOL EXTRACT TO ERADICATE WILD STRAIN CANDIDA ALBICANS BIOFILM - LESTARI, AYU DIAH; PUSPITAWATI, RIA; DJAIS, ARIADNA ADISATTYA (International Journal of Applied Pharmaceutics, 2019)
Objective: The pathogenic yeast Candida albicans forms biofilm to increase its resistance toward antifungal agents. Javanese turmeric is an Indonesian medicinal plant reported to have antifungal effects due to the active component, xanthorrhizol. The objective of this study was to measure the in vitro potential of Javanese turmeric ethanol extract to eradicate C. albicans biofilm. Methods: C. albicans was exposed to Javanese turmeric ethanol extract for 1 h during biofilm formation phases. MTT assay was used to test the percentage of biofilm eradication. Results: The minimum inhibitory concentration and minimum fungicidal concentration of Javanese turmeric ethanol extract against planktonic C. albicans were 15%. The minimum biofilm eradication concentration (MBEC50) was 25% in the early phase and 15% in the intermediate and maturation phases. Conclusions: Javanese turmeric ethanol extract is effective at eradicating clinical isolate of C. albicans biofilm.